A GUI-based numerical flow solver using the MacCormack’s scheme for Prandtl-Meyer expansion wave / Muhammad Imran Basseri - Basseri, Muhammad Imran (2017)
Prandtl-Meyer expansion fan is a flow phenomenon that occurs when a supersonic gas flows past through a convex comer, resulting in the formation of an expansion wave that consists of many Mach waves projected right at the comer. It is an inviscid, two-dimensional flow type that intended to be solved with the means of numerical methods in preference than its exact analytical solutions counterpart, thereby making it fall under the Computational Fluid Dynamics (CFD) subject. The flow solver for the governing Euler equations in strong conservation form will be based on the MacCormack’s predictor-corrector explicit finite difference method. The coding for the solution of the flow has been done with the aid of a personal computer using MATLAB r2015a version followed by validation procedures to ensure the agreement of the obtained results with the analytical solution results. Subsequently, GUI-based program was coded and developed by MATLAB Graphical User Interface Development Environment (GUIDE) to make the solver program easier to use since a well-designed graphical user interface can free the user from learning complex command languages to solve the flow problem themselves. The program’s main purpose is to be intuitive and serves as education software to assist students to learn and understand the flow phenomena produced by this wave in the desired flow field. User will be required to fill the inlet air properties and the solver will return two types of results, a Mach contour mesh grid representation and the air properties at any x- location in tabulated form.